Influence of climatic variables on the Aedes aegypti and Culex quinquefasciatus populations in Mato Grosso, Brazil - Lucinéia Claudia De Toni Aquino da Cruz; Alexander Gonçalves Ferreira Guimarães; Emerson Marques de Souza; Raquel da Silva Ferreira; Raphael de Souza Rosa Gomes; Renata Dezengrini Slhessarenko; Marina Atanaka (Revista da Sociedade Brasileira de Medicina Tropical, 2020)
Abstract INTRODUCTION: Aedes aegypti and Culex quinquefasciatus are vector species responsible for the transmission of important arboviruses. METHODS: Adult mosquitoes were collected in the urban areas of four municipalities in Mato Grosso within 1 year. RESULTS: A total of 19,110 mosquitoes were collected. Among them, 16,578 (86,8%) were C. quinquefasciatus (44% female and 56% male); 2,483 (13%), A. (Stegomyia) aegypti (54% female and 46% male); and 49 (0,30%), from the genus Psorophora, Anopheles, Coquilettidia, and Sabethes. A significant correlation was observed between the number of mosquitoes from all species and dew point (female mosquitoes, p = 0.001; male mosquitoes, p = 0.001). CONCLUSIONS: The results of this study may be used as environmental indicators of mosquito populations.